Magnetni monopoli v spinskem ledu - Klopčič, Urh (Matrika, 2023)
As elementary excitations in spin ice crystals, quasiparticles with magnetic charge or magnetic monopoles appear. This paper talks about common properties of spin ice, the emergence of magnetic monopoles within it and the thermodynamical description of the system. It is stressed that no discovery of an elementary particles violating Maxwell’s equations is presented. In the end, the effect of fractal dynamics of magnetic monpoles in spin ice on observable quantities is described.
Keywords: magnetic monopoles; magnetni monopoli; spin ice; spinski led